The factors associated with cardiorespiratory fitness status of students at Muhammadiyah 3 Senior High School Jakarta - Najran nisa; Anna Fitriani (ARGIPA (Arsip Gizi dan Pangan), 2020)
The status of cardiorespiratory fitness is an indicator of importance in measuring a person’s fitness. The status of fitness cardiorespiratory is the ability of a person in supplying the heart and lungs, spreading and using oxygen is influenced by several factors such as gender, intake of nutrients, and nutritional status. This research aimed to determine the factors related to the status of cardiorespiratory fitness of students at Muhammadiyah 3 Senior High School, Jakarta. Variables were sex, nutritional status (IMT/U), energy and macronutrient intake (carbohydrates, protein, fat), and micronutrients (zinc, iron, calcium, vitamin C) intake. This is a cross-sectional study, with 85 subjects. Data were analyzed using the Spearman Correlation test and Chi-Square test. Retrieval of cardiorespiratory fitness status data was measured by means of 20-meter shuttle run in a bleep test. The study showed that the majority of subjects were male. Most of subjects had less energy, carbohydrates, protein, fat, calcium, vitamin C, zinc, and iron. The statistical test showed that there were relationship between sex and nutritional status of IMT/U with the status of cardiorespiratory fitness (VO2max). There was no correlation between energy, carbohydrates, protein, fat, vitamin C, zinc, calcium, and iron intake with the status of cardiorespiratory fitness.